THE INFLUENCE OF LEG MUSCLE STRENGTH AND STATIC BALANCE ON SHOOTING IN PETANQUE SPORT - Massa, Resa Sukardi; Pulungan, Khoirul Anwar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
cochonnet/jack/boka while keeping the feet in a narrow circle. The main objectives of this research are to (1) determine the results of petanque shooting on leg muscle strength. (2) how static balance affects shooting results in petanque. (3) what are the results of shooting in a petanque match on leg muscle strength and static balance. This research was conducted in the lab. sports achievement and in the Gorontalo State University petanque field in March - June 2023. The method used is survey method with correlation technique. With total sampling technique, the sample numbered 20 people from a population of 20 people. Data analysis techniques used are simple correlation and regression techniques. The data analysis technique used is simple correlation and regression techniques. Based on the problems raised and supported by the description of terroritis, existing research data, and data analysis that has been carried out, it can be concluded that : 1). There is a significant relationship between leg muscle strength and shooting results as big as 0,4290 (42,90 %). 2) There is a significant relationship between static balance and shooting results as big as 0,4556 (45,56 %). 3) There is a significant relationship between leg muscle strength and static balance on shooting results as big as 0,6395 (63,95 %)